Recent advances of nanomaterial-based anti-angiogenic therapy in tumor vascular normalization and immunotherapy - Xiao, Mingshu; Shi, Yueli; Jiang, Sujing; Cao, Mengqing; Chen, Weiyu; Xu, Yun; Xu, Zhiyong; Wang, Kai (Frontiers in Oncology, 2022)
Anti-angiogenesis therapy and immunotherapy are the first-line therapeutic strategies for various tumor treatments in the clinic, bringing significant advantages for tumor patients. Recent studies have shown that anti-angiogenic therapy can potentiate immunotherapy, with many clinical trials conducted based on the combination of anti-angiogenic agents and immune checkpoint inhibitors (ICIs). However, currently available clinical dosing strategies and tools are limited, emphasizing the need for more improvements. Although significant progress has been achieved, several big questions remained, such as how to achieve cell-specific targeting in the tumor microenvironment? How to improve drug delivery efficiency in tumors? Can nanotechnology be used to potentiate existing clinical drugs and achieve synergistic sensitization effects? Over the recent few years, nanomedicines have shown unique advantages in antitumor research, including cell-specific targeting, improved delivery potentiation, and photothermal effects. Given that the applications of nanomaterials in tumor immunotherapy have been widely reported, this review provides a comprehensive overview of research advances on nanomaterials in anti-angiogenesis therapy, mainly focusing on the immunosuppressive effects of abnormal tumor vessels in the tumor immune microenvironment, the targets and strategies of anti-angiogenesis nanomedicines, and the potential synergistic effects and molecular mechanisms of anti-angiogenic nanomedicines in combination with immunotherapy, ultimately providing new perspectives on the nanomedicine-based synergy between anti-angiogenic and immunotherapy.